Emergence of Sequence Type 779 Methicillin-Resistant Staphylococcus aureus Harboring a Novel Pseudo Staphylococcal Cassette Chromosome mec (SCCmec)-SCC-SCC(CRISPR) Composite Element in Irish Hospitals - Kinnevey, Peter M. (American Society for Microbiology, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) has been a major cause of nosocomial infection in Irish hospitals for 4 decades, and replacement of predominant MRSA clones has occurred several times. An MRSA isolate recovered in 2006 as part of a larger study of sporadic MRSA exhibited a rare spa (t878) and multilocus sequence (ST779) type and was nontypeable by PCR- and DNA microarray-based staphylococcal cassette chromosome mec (SCCmec) element typing. Whole-genome sequencing revealed the presence of a novel 51-kb composite island (CI) element with three distinct domains, each flanked by direct repeat and inverted repeat sequences, including (i) a pseudo SCCmec element (16.3 kb) carrying mecA with a novel mec class region, a fusidic acid resistance gene (fusC), and two copper resistance genes (copB and copC) but lacking ccr genes; (ii) an SCC element (17.5 kb) carrying a novel ccrAB4 allele; and (iii) an SCC element (17.4 kb) carrying a novel ccrC allele and a clustered regularly interspaced short palindromic repeat (CRISPR) region. The novel CI was subsequently identified by PCR in an additional 13 t878/ST779 MRSA isolates, six from bloodstream infections, recovered between 2006 and 2011 in 11 hospitals. Analysis of open reading frames (ORFs) carried by the CI showed amino acid sequence similarity of 44 to 100% to ORFs from S. aureus and coagulase-negative staphylococci (CoNS). These findings provide further evidence of genetic transfer between S. aureus and CoNS and show how this contributes to the emergence of novel SCCmec elements and MRSA strains. Ongoing surveillance of this MRSA strain is warranted and will require updating of currently used SCCmec typing methods.